The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/cryst11091138
|View full text |Cite
|
Sign up to set email alerts
|

Pressure- and Temperature-Dependent Crystallization Kinetics of Isotactic Polypropylene under Process Relevant Conditions

Abstract: In this study, a non-nucleated homopolymer (HP) and random copolymer (RACO), as well as a nucleated HP and heterophasic copolymer (HECO) were investigated regarding their crystallization kinetics. Using pvT-measurements and fast scanning chip calorimetry (FSC), the crystallization behavior was analyzed as a function of pressure, cooling rate and temperature. It is shown that pressure and cooling rate have an opposite influence on the crystallization temperature of the materials. Furthermore, the addition of nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The HTC ranges are chosen in reference to the default Moldflow values ( HTC filling = 5000W/m 2• C , HTC packing = 2500W/m 2• C ). As for the pressure-dependent viscosity model parameter, the variation range goes from 0 up to 0.4 K/MPa in order to cover the actual behavior of POM and other typical semicrystalline thermoplastics such as PP [42].…”
Section: Simulation Environmentmentioning
confidence: 99%
“…The HTC ranges are chosen in reference to the default Moldflow values ( HTC filling = 5000W/m 2• C , HTC packing = 2500W/m 2• C ). As for the pressure-dependent viscosity model parameter, the variation range goes from 0 up to 0.4 K/MPa in order to cover the actual behavior of POM and other typical semicrystalline thermoplastics such as PP [42].…”
Section: Simulation Environmentmentioning
confidence: 99%
“…However, the crystallization temperature of iPP during cooling increases with the increasing pressure. Recently, a shift factor of 0.23-0.26 • C/MPa at cooling rates of 0.1-7 • C/min was determined [30,31]. Mezghani and Phillips [32] elaborated a temperature-pressure phase diagram for the αand γ-forms of iPP, and also determined the increase in the equilibrium melting temperature (T m 0 ) of both forms with the increasing pressure as well as the pressure dependence of the transition temperature between the αand γ-domains.…”
Section: Introductionmentioning
confidence: 99%
“…At present, in addition to the review, 14 regular articles [2][3][4][5][6][7][8][9][10][11][12][13][14][15] have been published on the special topic of "polymer crystallization". These contributions span research topics ranging from molecular mechanisms of nucleation and nucleating agents to the effect of molecular structures, chain conformations and processing parameters on the nucleation and crystallization behavior of various polymers.…”
mentioning
confidence: 99%
“…The polymorphic transition probably resulted from a gauche to trans flow-induced conformation transition. Kuehnert et al [10] analyzed the crystallization kinetics of four grades of polypropylene (with and without nucleating agents) at different temperatures and under various pressures via PVT-measurements and fast scanning chip calorimetry. It was observed that the pressure-dependent shift factor of the crystallization temperature was independent of the material.…”
mentioning
confidence: 99%